2001
DOI: 10.1097/00008877-200107000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in behavioral responses to novelty and amphetamine self-administration in male and female rats

Abstract: Previous work has shown that individual differences in locomotor activity in an inescapable novel environment can predict acquisition of amphetamine self-administration. The current study examined whether individual differences in approach to novelty in a free choice test could also predict amphetamine self-administration. Further, the current study examined whether individual differences in either free choice or inescapable novelty tests could predict responding for a nondrug reinforcer (sucrose) in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
126
5
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(151 citation statements)
references
References 32 publications
(33 reference statements)
18
126
5
2
Order By: Relevance
“…One prominent example is a study demonstrating that the diagnostic criteria for addiction could be modeled in rats (25). With the emergence of this animal model of "addiction," it was reported that locomotor response to novelty-or "sensation-seeking" as measured in the rat-is not associated with addiction liability per se (21,25,50), but does remain a good predictor of the initial propensity to take drugs (22,51). Although the design of the present study did not permit phenotypic differences to emerge in the acquisition of drug-taking behavior as it is typically assessed (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…One prominent example is a study demonstrating that the diagnostic criteria for addiction could be modeled in rats (25). With the emergence of this animal model of "addiction," it was reported that locomotor response to novelty-or "sensation-seeking" as measured in the rat-is not associated with addiction liability per se (21,25,50), but does remain a good predictor of the initial propensity to take drugs (22,51). Although the design of the present study did not permit phenotypic differences to emerge in the acquisition of drug-taking behavior as it is typically assessed (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Erb and Parker (1994) using a different novelty procedure and a different psychostimulant found no relationship between the strength of amphetamine place conditioning and responding in the novel environment. However, the data with amphetamine are more complex, since there is some evidence that place preference for amphetamine-associated cues could be predicted by reactivity to novelty (Klebaur and Bardo 1999;Klebaur et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Rodent locomotor response to a novel environment predicts the propensity to self-administer a variety of drugs of abuse (Piazza et al, 1990;Grimm and See, 1997;Klebaur et al, 2001;Suto et al, 2001). Sensitization of the locomotor response to amphetamine, cocaine, and morphine is more robust when drug is administered in a novel environment than when it is administered in the home cage (Badiani et al, 1995(Badiani et al, , 2000Fraioli et al, 1999).…”
Section: Data Suggest a Novelty-d3 Da Receptor Interactionmentioning
confidence: 99%